Intelligent algorithms for six degrees of freedom robot trajectory planning considering vibration suppression. Issue 1 (1st November 2022) - Li, fazhe; Cao, Jiayong; Wu, shihao; Wu, peihua; Zhu, ziwei
Abstract: The residual vibration of the flexible joint manipulator during and after the movement will seriously affects the positioning accuracy of the manipulator. This paper discusses the trajectory planning method for suppressing the joint vibration. A trajectory optimal model which contains the minimization of both time and jerk was proposed. An optimization method based on comprehensive learning particle swarm optimization (CLPSO) algorithm was utilized for solving the optimal problem. Compared with other optimal solution method, CLPLO has the advantages of avoiding premature convergence. A numerical simulation case shows that the optimal trajectory obtained in this paper generated less joint vibration. The effectiveness of the proposed method was verified to some extent.